Comparative transcriptomic analysis of the malaria parasites Plasmodium falciparum and Plasmodium vivax sensitive and resistant strains - S. Sakpal; S. Z. Abdeen; Sh. L. Kothari; V. Bastikar (Разработка и регистрация лекарственных средств)
Introduction. Malaria is the sixth leading cause of death worldwide. According to a WHO survey (2019-2020), the total number of malaria deaths is estimated to be 409000. Plasmodium falciparum and Plasmodium vivax are major malaria parasites, particularly in subtropical areas.Materials and methods. In the present study, we used a transcriptome analysis of raw RNA sequence data to identify and characterize the differentially expressed genes in Plasmodium falciparum chloroquine-sensitive and chloroquine-resistant strains, as well as Plasmodium vivax primaquine sensitive and primaquine resistant strains. The raw RNA sequence data were obtained from the NCBI SRA database using the Accession IDs PRJNA308455, SRR14191963, and SRR332573.Results and discussion. The sequence of raw RNA was quantified, mapped, and annotated. The total number of reads mapped to the reference genome for Plasmodium falciparum was found to be 45474448 and for Plasmodium vivax was 38226870. The Cufflinks-Cuffdiff tool was used to identify differentially expressed genes in Plasmodium falciparum and Plasmodium vivax sensitive and resistant strains. This differentially expressed gene was further annotated and plotted using the "Limma" package of Bioconductor. The PPI network was constructed in String Database and Cytoscape software. Pathway enrichment analysis of list differentially expressed gene performed using KEGG and GO tool.Conclusion. In sensitive and resistant strains, comparative transcriptome analysis revealed differentially regulated gene expression patterns.